2017
DOI: 10.1021/acs.analchem.7b01244
|View full text |Cite
|
Sign up to set email alerts
|

Identification of GalNAc-Conjugated Antisense Oligonucleotide Metabolites Using an Untargeted and Generic Approach Based on High Resolution Mass Spectrometry

Abstract: Antisense oligonucleotides linked by phosphorothioates are an important class of therapeutics under investigation in various pharmaceutical companies. Antisense oligonucleotides may be coupled to high-affinity ligands (triantennary N-acetyl galactosamine = GalNAc) for hepatocyte-specific asialoglycoprotein receptors (ASGPR) to enhance uptake to hepatocytes and to increase potency. Since disposition and biotransformation of GalNAc-conjugated oligonucleotides is different from unconjugated oligonucleotides, appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
41
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 24 publications
4
41
0
Order By: Relevance
“…As identified by Husser et al (2017), we also confirmed the distinguishable MS/MS product ions (i.e. PO 3 − , H 2 PO 4 − , and PO 2 S − fragment ions) in the PO‐ and PS‐containing oligonucleotides (Figure 3).…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…As identified by Husser et al (2017), we also confirmed the distinguishable MS/MS product ions (i.e. PO 3 − , H 2 PO 4 − , and PO 2 S − fragment ions) in the PO‐ and PS‐containing oligonucleotides (Figure 3).…”
Section: Resultssupporting
confidence: 89%
“…With the high‐quality separation of the method, metabolite identification was performed readily for each compound without effort to avoid assignments due to the overlapping of m/z series from multiple metabolites with similar retention times. Accurate quantifications have been unavailable due to the variance of ionization efficiency for metabolites and the absence of standards for all metabolites (Husser et al, 2017). However, to estimate the relative amounts of each compound in a timely manner, the signal intensities of compounds were optimized using internal standards.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, chemically modified single-strand oligonucleotides usually possess relatively low membrane permeability, and limited stability during the long-term therapy [ 12 ]. To address those issues, the single-strand oligonucleotides were either conjugated with functional ligands, polymers, and nanoparticles [ 13 , 14 ], or complexed with cationic polymers, liposomes, and nanomaterials [ 15 ] to increase their cell internalization, stability, and transfection efficiency. Cationic polymers with various chemical structures have widely used for intracellular delivery of biomolecules such as genes and proteins [ 16 – 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, since GalNAc is an excellent ligand of a sialoglycoprotein receptor, it was also used to deliver bioactive antisense oligonucleotides in liver through interaction with membrane hepatocytes. 5 On the other hand, some rare polysaccharides analyzed by NMR spectroscopy have been found to contain GalNAc in a furanose form. For instance, the O-specific polysaccharide produced by Proteus penneri strain 22, responsible for urinary tract infections with subsequent complications, presents a Galf NAc residue linked to the 4-position of a glucuronic acid entity.6 Moreover, the Gram negative bacteria Campylobacter jejuni 11168, responsible for serious gastroenteritis, is able to biosynthesize a chain (containing…”
Section: Introductionmentioning
confidence: 99%